Laplace Transform of Fourier Series Functions of a Period P = 2π (Global Journal of Science Frontier Research, 2019)
The authors establish a set of presumably new results, Which transform a periodic functions of period p = 2 to new functions. So in this paper, the authors tries to evaluate Laplace transform of the discontinuous and periodic function that involves in some applications of non-homogeneous differential equations in Physics, electrical engineering, and other many disciplines. Hence, such type of functions expands to a Fourier series, which represent complicated and discontinuous regarding of simpler continuous and periodic functions of cosines and sines.
Keywords: entomocidal; solar radiation; assessment; callosobruchus maculatus.